Rethinking Asceticism in Nietzsche with Zhuangzi: A Physio-Psychological Perspective - Manhua Li (Religions, 2024)
This article proposes a reconsideration of the physio-psychological dimension of the notion of asceticism in Nietzsche in the light of classical Daoist philosophy. Nietzsche famously criticises the nihilistic ascetic ideal for negating the body-self (Leib-Selbst) in the Christian religion as well as in Socratic metaphysics. Nietzsche critiques the metaphysical language that presupposes an opposition between the good (as the useful) and the evil (as the useless). However, the Nietzschean ascetic person who says yes to life remains mostly conceptual within the philosophical framework where physio-psychology stands as the superior form of thinking. To contrast such asceticism that bears traces of Greek Stoicism and Epicureanism, I argue that Zhuangzi’s self-cultivating practices such as mind-fasting (xinzhai 心齋) can be incorporated into the Nietzschean physio-psychological notion of asceticism that goes beyond askesis with Stoic and Epicurean therapeutic connotations, given that both Zhuangzi and Nietzsche are more concerned with cultivating a lived body rather than purifying souls.